Case Report and X-ray Microtomography and Scanning Electron Microscopy Analysis of Teeth with Hypocalcified Amelogenesis Imperfecta - Marinoni, Rodrigo W; Silva, Thiago G; Benato, Leonardo S; Rumbelsperger, Anelize M B; de Lima, Antonio Adilson Soares (Journal of Dentistry Indonesia, 2023)
Amelogenesis imperfecta (AI) is a genetic disease characterized by producing morphological and structural changes in tooth enamel. Objective: To highlight the morphological changes observed in teeth with hypocalcified AI based on scanning electron microscopy and microtomography analysis. Case report: An adult male had teeth seriously compromised by hypocalcified AI. The treatment plan involved removal of third molars followed by restorative and prosthetic treatment. After extraction, the teeth were analyzed by SEM and X-ray microtomography (microCT). Teeth with AI revealed the presence of microfractures arranged from the outer surface to the center of the enamel. Microfractures had a cracked or “cracked ground” pattern. SEM confirmed the presence of microfractures and distortion in the orientation of the enamel prisms in some regions. Conclusion: Teeth of patients with hypocalcified amelogenesis imperfecta IIIA subtype show significant structural changes that are closely related with the ease of fractures.